Sympatric breeding occurrence of two call types of Evening Grosbeak in Western Wyoming - Duman, Konshau W.; Hahn, Thomas P. (Frontiers in Bird Science, 2024)
The Evening Grosbeak is a species with multiple vocally distinct recognized groups known as call types. The range boundaries and degrees of overlap between these groups remain an area of continuing research. We report sympatric breeding occurrence of Evening Grosbeaks of call type 1 and call type 4 in the Jackson Hole area of Wyoming, and we show that these two call types have been overlapping in this region for at least 24 years. We also note a major increase in the local abundance of Evening Grosbeaks in 2023 compared to past years. These findings suggest that the range boundary between these two call types is relatively consistent at this short time scale, but it may fluctuate somewhat given changes in the proportions of the two types over this period. We detected both call types continuously through the 2023 breeding period in the Jackson Hole area, and we had breeding season detections of both types in the area in